A new distributed energy system configuration for cooling dominated districts and the performance assessment based on real site measurements. (February 2019) - Kang, Jing; Wang, Shengwei; Yan, Chengchu
Abstract: In this paper, a new configuration of distributed energy system (DES), which integrates a district cooling system, is proposed as a new energy-efficient technology to be used in cooling dominated districts. An optimal design approach is developed for DES design and operation scheduling by using the real site measurements of energy demands. A case study on the DES in a high density district, i.e., a university campus in Hong Kong, is performed. The energy and economic performance of the DES, the matching performance of on-site generations and the efficiency of electric chillers are analyzed and compared with that of the centralized energy system (CES). It can be found that the proposed DES is a cost-effective and energy-efficient technology for the regions concerned. The DES contributes to substantial primary energy saving of 9.6% and a significant reduction in the operating cost of 44%. The distributed generations in the DES can match electricity demand very well around the year while the absorption chillers can match cooling demand well in transition months. Compared with the CES, the DES allows electric chillers of larger capacities to be used and to operate at higher part load ratios, resulting in higher energy efficiency in operation. Highlights: A new configuration of DES integrating a district cooling system is proposed. The DES performance is assessed by comparison with CES based on the real-site measurements. DES reduces substantial primary energy consumption (9.6%) and operating cost (44%). Distributed generation can match the electricity demand very well all year round. The cooling efficiency is improved significantly by using DCS in a high demand density district.